Development of an Ultrasonic Pest Repellent System Based on ESP32 and the Internet of Things (IoT) - Siti Fatimah; Inda Lestari; Cyndi Lestari; Nadia Putri Larita; Dini Milatul Husniyah; Arini Rosa Sinensis; Thoha Firdaus (Justek : Jurnal Sains dan Teknologi, 2026)
Pest attacks on agricultural land often result in a significant decrease in crop yields. This study aims to develop an IoT-based pest repellent system integrating ultrasonic waves and remote control. The method involves an ESP32 microcontroller, a PIR sensor, and a PAM8403 amplifier with a piezoelectric tweeter. The system was evaluated through laboratory calibration and real-field implementation in East OKU. This device features automatic mode (ultrasonic triggers >20 kHz) and manual mode via the Blynk application. Quantitative results show a maximum detection range of 5 meters with a 110-degree coverage angle. The system achieves a stable 30 kHz output and real-time notifications with an average latency of less than 1 second. IoT integration enables farmers to monitor and control the device remotely, increasing crop protection efficiency in dynamic rice field environments.